Mirage events & driver haptic steering alerts in a motion-base driving simulator: A method for selecting an optimal HMI. (November 2017) - Talamonti, Walter; Tijerina, Louis; Blommer, Mike; Swaminathan, Radhakrishnan; Curry, Reates; Ellis, R. Darin
Abstract: This paper describes a new method, a 'mirage scenario, ' to support formative evaluation of driver alerting or warning displays for manual and automated driving. This method provides driving contexts (e.g., various Times-To-Collision (TTCs) to a lead vehicle) briefly presented and then removed. In the present study, during each mirage event, a haptic steering display was evaluated. This haptic display indicated a steering response may be initiated to drive around an obstacle ahead. A motion-base simulator was used in a 32-participant study to present vehicle motion cues similar to the actual application. Surprise was neither present nor of concern, as it would be for a summative evaluation of a forward collision warning system. Furthermore, no collision avoidance maneuvers were performed, thereby reducing the risk of simulator sickness. This paper illustrates the mirage scenario procedures, the rating methods and definitions used with the mirage scenario, and analysis of the ratings obtained, together with a multi-attribute utility theory (MAUT) approach to evaluate and select among alternative designs for future summative evaluation. Highlights: A new method called 'mirage scenario' is introduced to support formative evaluation. The mirage scenario provides driving contexts briefly presented and then removed. During each mirage event a haptic steering display was evaluated. Each haptic display indicated a steering response may be executed for obstacle avoidance. Methods to select among alternative designs for future summative evaluation are given.